2020
DOI: 10.1534/genetics.119.302896
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Fate Switch in theCaenorhabditis elegansSeam Cell Lineage Occurs Through Modulation of the Wnt Asymmetry Pathway in Response to Temperature Increase

Abstract: Populations often display consistent developmental phenotypes across individuals despite inevitable biological stochasticity. Nevertheless, developmental robustness has limits, and systems can fail upon change in the environment or the genetic background. We use here the seam cells, a population of epidermal stem cells in Caenorhabditis elegans, to study the influence of temperature change and genetic variation on cell fate. Seam cell development has mostly been studied so far in the laboratory reference strai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…However, not all cell divisions that give rise to the 959 somatic cells are completely invariant. Studies have identified several lineages, including the vulva, where environmental stressors, genetic mutations and/or genetic divergence of wild isolates leads to stochastic changes in a highly invariant cell fate pattern ( Braendle and Félix, 2008 ; Hintze et al, 2020 ; Katsanos et al, 2017 ). Thus, we wondered if the CDK sensor generated here could be utilized to visualize and predict stochastic lineage decisions during C. elegans development.…”
Section: Resultsmentioning
confidence: 99%
“…However, not all cell divisions that give rise to the 959 somatic cells are completely invariant. Studies have identified several lineages, including the vulva, where environmental stressors, genetic mutations and/or genetic divergence of wild isolates leads to stochastic changes in a highly invariant cell fate pattern ( Braendle and Félix, 2008 ; Hintze et al, 2020 ; Katsanos et al, 2017 ). Thus, we wondered if the CDK sensor generated here could be utilized to visualize and predict stochastic lineage decisions during C. elegans development.…”
Section: Resultsmentioning
confidence: 99%
“…S2 ). However, seam cell number and variance in wild type is mildly increased at 25 °C compared to 20 °C as previously reported 10 , therefore we chose to use 20° as the temperature for all our experiments.…”
Section: Resultsmentioning
confidence: 91%
“…( k – l ) Loss of cell contact between V2 and V3 daughter cells in eff-1(icb4) at the L2 asymmetric cell division ( k ), marked with an arrowhead, in comparison to wild-type ( l ). Seam cells are visualised using the scm::GFP marker, as well as seam cell driven membrane-targeted GFP (GFP::CAAX) 10 ) ( e – j ) or ajm-1p::ajm-1::GFP ( k – l ). Scale bars in a-h, k and l are 20 µm and in i-j 100 µm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single molecule FISH was performed as previously described ( Hintze et al., 2020 ; Katsanos et al., 2017 ). Briefly, animals were synchronized by bleaching and treated with extract for 1 hour at mid-L2 stage.…”
Section: Methodsmentioning
confidence: 99%